Hubungan Pengetahuan, Sikap Ibu Postpartum dan Dukungan Keluarga dengan Pelaksanaan Inisiasi Menyusu Dini (IMD) - Karmika, Ni Nyoman Kalih; Rahayu, Sri; Yuni Rahyani, Ni Komang (Midwifery Care Journal, 2026)
Early initiation of breastfeeding (IMD) involves breastfeeding immediately after birth, usually within 30 minutes to one hour. Babies are given the opportunity to initiate breastfeeding immediately after birth by allowing skin-to-skin contact with the mother for at least an hour or more, until the first feeding is complete. Several factors that affect the implementation of IMD are knowledge factors, maternal attitudes and family support. The purpose of this study is to determine the relationship between knowledge, attitudes of postpartum mothers and family support with the implementation of early breastfeeding initiation at UPTD BLUD Puskesmas Praya Central Lombok. The type of research is quantitative, descriptive analytical method, with a cross-sectional research design. The study population of all mothers who gave birth was normal at the time of the study. The research sample was determined by the Total Sampling technique. The number of samples was 36 people. Data collection using questionnaires.  The results of the study showed that the majority of respondents had good knowledge as many as 35 people (97.22%), 34 people (94.40%) agreed and 32 people (89.90%) had family support. The analysis of the research data using the Rank Spearman test, the results were knowledge p (0.011) < α (0.05), attitude p (0.000) < α (0.05) and family support p (0.027) < α (0.05). The conclusion of this study is that there is a relationship between knowledge, attitudes of postpartum mothers and family support with the implementation of Early Breastfeeding Initiation at UPTD BLUD Puskesmas Praya.  The results of this study are expected to increase knowledge, attitudes and family support regarding the importance of IMD for the success of exclusive breastfeeding and the growth and development of children